2011
DOI: 10.1017/s1047951111000795
|View full text |Cite
|
Sign up to set email alerts
|

Right bundle branch block as a marker for interatrial septal abnormalities

Abstract: Right bundle branch block should serve as a valuable indicator to motivate a detailed search for interatrial septal abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
0
7
3
Order By: Relevance
“…RBBB quite frequently occurs with PFO in healthy people and can even be used as a marker for PFO 30. PFO can be a problem for other recreational sports as well, such as recreational diving, which is becoming more and more popular, and also requires a Valsalva maneuver.…”
Section: Discussionmentioning
confidence: 99%
“…RBBB quite frequently occurs with PFO in healthy people and can even be used as a marker for PFO 30. PFO can be a problem for other recreational sports as well, such as recreational diving, which is becoming more and more popular, and also requires a Valsalva maneuver.…”
Section: Discussionmentioning
confidence: 99%
“…For the follow-up analysis of LA volumes, TTE is typically used, but 3D techniques, such as real-time 3D echocardiography (Zhang et al, 2017), multi-slice CT (Polaczek et al, 2019) and MRI (Tsao et al, 2005), especially LGE MRI (McGann et al, 2014), may provide more accurate information. For the measurement of LA wall thickness, TEE provides high spatial resolution and has been used by Bakalli et al (2012). CT is an ideal modality, thanks to its high resolution, and MRI is widely considered to be the gold standard for the viability assessment of wall pathology (Karim et al, 2018).…”
Section: Imaging During Ablation Proceduresmentioning
confidence: 99%
“…More accurate diagnostic aspects may characterize this association as mutually dependent changes. Moreover, CRBBB in childhood and teenagehood could be a relevant indicator to motivate the search for abnormalities in atrial septum as it occurs in ASD, POF or aneurysm, changes found in approximately 80% of these cases 1 . In this context, it is unknown the association of LAHB, found in this patient.…”
Section: Complementary Testsmentioning
confidence: 99%